OPTIMALISASI STRATEGI FUNDRAISING WAKAF UANG TERHADAP PENAMBAHAN JUMLAH WAKIF - Sugianto Effendi; Jafril Khalil (STIT AL-AMIN KREO TANGERANG, 2023)
This paper discusses appropriate strategic alternatives in optimizing cash waqf products in Hasanah Waqf. This paper departs from the existence of several obstacles faced by Wakaf Hasanah as a collector of cash waqf so that this product has not experienced a significant increase. In this study the authors used SWOT analysis to determine internal factors and external factors related to the application of these products and appropriate alternative strategies. The results showed that the appropriate strategic alternatives were developing cash waqf operations through pilot projects, establishing business partnerships with other parties, approaching waqif candidates both religiously and socially, creating products with new innovations that could become a source of funding for business units; cooperate with regulators to increase public trust in waqf institutions, improve the quality of nazhir and increase socialization and education of cash waqf to prospective waqif (community).